Severe hypophosphatemia as the initial presentation of renal Fanconi's syndrome and distal renal tubular acidosis related to zoledronic acid: A case report and literature review - Yujia Wu; Tiantian Ma; Xiaojuan Yu; Tao Su (Karger Publishers, 2022)
Introduction: Zoledronic acid (ZA) is a widely used bisphosphonate compound for the prevention of skeletal metastasis-associated osteolysis and treatment of post-menopause osteoporosis. Acute kidney injury is one of the commonly described renal complications. Electrolytes disorder has also been reported relevant to ZA exposure and nephrotoxicity. Syndrome of persistent hypophosphatemia, hypokalemia and metabolic acidosis is regarded as the initial signs of acute kidney injury. Case presentation: We reported a 64-year-old female with bone metastasis from lung adenocarcinoma who received a 5-year history of 4-week cycle ZA infusion. She initially presented symptomatic severe hypophosphatemia and was finally identified with ZA-induced generalized tubular dysfunction as Fanconi's syndrome and distal renal tubular acidosis. Renal pathological findings revealed toxic renal tubular necrosis. The ZA infusion was thus extended to an 8-week cycle with oral phosphate supplementation and alfacalcidol. Although periodic changes pre- and post-ZA infusion existed yet, hypophosphatemia was effectively improved and the rapid decline of eGFR was partially delayed. We reviewed the literature and mainly summarized the characteristics of bisphosphonates-associated hypophosphatemia. Moderate hypophosphatemia was more frequently mentioned in contrast to severe cases being predisposed to be reported. And progressive hypophosphatemia serves as an early sign of kidney injury. Conclusion: Progressive electrolyte disorders and CKD were the long-term renal outcome of the current patient. We would like to arouse more attention to electrolytes imbalance related to early ZA-induced kidney injury and emphasize the significance of close monitoring.